Design and Development of a Monitoring and Controlling System for Automatic Watering and Filling in Fungi House's Internet of Things-Based Mushroom Cultivation - Supriyanto, Eko; Rochmatika, Rizkha Ajeng; Oktaviani, Cantika Cakhya; Luqita, Syauqi Fajar; Hasan, Abu; Bramantyo, Hutama Arif; Yudantoro, Tri Raharjo (Politeknik Negeri Semarang, 2024)
Temperature and humidity are aspects that need to be considered in cultivating oyster mushrooms. Previously, Fungi House in Genting Village, Semarang, implemented an automatic temperature, humidity, and watering monitoring system, but manually filled the water. This new system's design and development aim to simplify the monitoring and control of temperature, humidity, and water level for managers. Managers determined temperature, humidity, and water level thresholds via the web page. This system used the agile scrum method. The test results showed that the temperature measurement accuracy was 96.85%, humidity 99.35%, and water level 98.99%. With this system, the quality of baglog (mushroom growing medium) increased by 4.62%, while dead baglog decreased by 99.01%. Black box testing demonstrates that all features perform well in web testing. In the load activity test, with low bandwidth (6.71 Mbps), the average load time was 1.32 seconds, and with high bandwidth (37.15 Mbps), it was 0.878 seconds. These two conditions indicate excellent system performance and provide optimal user experience.